2013
DOI: 10.1021/mp400571a
|View full text |Cite
|
Sign up to set email alerts
|

Improving Lithium Therapeutics by Crystal Engineering of Novel Ionic Cocrystals

Abstract: Current United States Food and Drug Administration (FDA)-approved lithium salts are plagued with a narrow therapeutic window. Recent attempts to find alternative drugs have identified new chemical entities, but lithium’s polypharmacological mechanisms for treating neuropsychiatric disorders are highly debated and are not yet matched. Thus, re-engineering current lithium solid forms in order to optimize performance represents a low cost and low risk approach to the desired therapeutic outcome. In this contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 64 publications
(102 reference statements)
0
83
0
Order By: Relevance
“…The solutions kept upon standing up to complete solvent matrix evaporation were prepared by dissolution of lamivudine (or zalcitabine in 5) either in isopropyl alcohol (1,(3)(4)(5) or directly in a 0.28 mol L −1 solution of hydrochloric acid in water (2). Except for the preparation of 2, a next step consisted of addition of another aqueous solution of either 0.28 mol L −1 hydrochloric acid only (1 and 5) or both 0.28 mol L −1 hydrochloric acid and 0.04 mol L −1 maleic acid (3).…”
Section: Preparation Of Multicomponent Molecular Crystal Forms 1-5mentioning
confidence: 99%
“…The solutions kept upon standing up to complete solvent matrix evaporation were prepared by dissolution of lamivudine (or zalcitabine in 5) either in isopropyl alcohol (1,(3)(4)(5) or directly in a 0.28 mol L −1 solution of hydrochloric acid in water (2). Except for the preparation of 2, a next step consisted of addition of another aqueous solution of either 0.28 mol L −1 hydrochloric acid only (1 and 5) or both 0.28 mol L −1 hydrochloric acid and 0.04 mol L −1 maleic acid (3).…”
Section: Preparation Of Multicomponent Molecular Crystal Forms 1-5mentioning
confidence: 99%
“…4 (4) ], comparing with À168.2 (3) in polymorph 1 and 179.3 (1) in the structure of the parent salicylic acid (Munshi & Guru Row, 2006). In all of the salicylate structures, including those of the anhydrous Li salt (Smith et al, 2013), the Li monohydrate salt (Wiesbrock & Schmidbaur, 2003b) and the K and Rb salt (Dinnebier et al, 2002) or salt adducts (Downie & Speakman, 1953), a short intramolecular phenolic O-HÁ Á ÁO carboxyl hydrogen bond is present. Symmetry codes: (i) x; y; z þ 1; (ii) x À 1; y; z þ 1; (iii) Àx þ 1; Ày þ 1; Àz þ 1.…”
Section: Structure Descriptionmentioning
confidence: 95%
“…Even more recently, we reported the first organic anion (B -= salicylate and nicotinate) lithium ICCs with Lproline as a coformer. 29 Moreover, we reported that the blood and brain pharmacokinetics (PK) of one ICC, that of lithium salicylate and proline (LISPRO), are drastically different than the most commonly prescribed FDA approved lithium salt, lithium carbonate, in rats. Importantly, 6 we also demonstrated that this new speciation of lithium did not negatively affect the bioactivity of lithium in clinically relevant in vitro models.…”
Section: Introductionmentioning
confidence: 99%